White Fragility: Why It's so Hard for White People to Talk about Racism. Issue 2 (3rd April 2019) - Andersen, Kent
Abstract: In White Fragility, Robin DiAngelo deploys social reproduction theory to identify and account for the phenomenon she calls white fragility : the patterns of perceptions and behaviors exhibited by white people when confronted with evidence that they have perpetrated racism or perpetuated systems of racial inequality. These patterns and perceptions function to maintain and reinforce the racial status quo and insulate white people from self-examination. While not directly addressed to higher education professionals, DiAngelo's argument offers educators and administrators an opportunity for reflection and enhanced developmental practice in their work.